Konstruksi Pertimbangan Hakim dalam Penerapan Prinsip Kebaruan (Novelty) pada Penyelesaian Sengketa Desain Industri - Kurniawan, Adi (Direktorat Jenderal Peraturan Perundang-undang, Kementerian Hukum dan Hak Asasi Manusia, 2022)
Abstract The principle of novelty that applied on industrial design dispute settlement in Indonesia and United States of America shows that the principle of novelty applied based on Article 25:1 TRIPs Agreement. In TRIPs Agreement, interpretation method that used based on ‘significantly differ’. The Panel of Judges at Supreme Court judged that the comparison between the design of the motorcycle industry garuda owned by the Defendant did not significantly differ from the design of the motorcycle industry owned by plaintiff. In the United States, in interpreting novelty, the Court constructed the design by implementing